2010
DOI: 10.1097/nnr.0b013e3181eb31f6
|View full text |Cite
|
Sign up to set email alerts
|

Shared Risk Factors for Distinct Geriatric Syndromes in Older Taiwanese Inpatients

Abstract: The findings support the theory that common geriatric syndromes have a shared set of risk factors-female gender, depressive symptoms, and functional, cognitive, and nutritional status. Revising care to target these shared risk factors in preventing common geriatric syndromes is theoretically sound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
0
19
0
3
Order By: Relevance
“…However, the interaction between multiple geriatric syndromes and life satisfaction as well as the accumulated effects of multiple geriatric syndromes on life satisfaction remain unexplored. Several demographic characteristics, such as age (Inouye et al, 2007), sex (Chen, Dai, Yen, Huang, & Wang, 2010), education level (Brown, Kiely, Bharel, & Mitchell, 2013), self-rated health (Bluestein & Rutledge, 2006), and chronic diseases (Lee, Cigolle, & Blaum, 2009;Mohile et al, 2011), have been associated with geriatric syndromes, and these factors could influence the association between geriatric syndromes and life satisfaction. By using data obtained from a national representative sample, we analyzed the relationship between multiple geriatric syndromes and life satisfaction in community-dwelling older adults, and the impact of socio-demographic factors on this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interaction between multiple geriatric syndromes and life satisfaction as well as the accumulated effects of multiple geriatric syndromes on life satisfaction remain unexplored. Several demographic characteristics, such as age (Inouye et al, 2007), sex (Chen, Dai, Yen, Huang, & Wang, 2010), education level (Brown, Kiely, Bharel, & Mitchell, 2013), self-rated health (Bluestein & Rutledge, 2006), and chronic diseases (Lee, Cigolle, & Blaum, 2009;Mohile et al, 2011), have been associated with geriatric syndromes, and these factors could influence the association between geriatric syndromes and life satisfaction. By using data obtained from a national representative sample, we analyzed the relationship between multiple geriatric syndromes and life satisfaction in community-dwelling older adults, and the impact of socio-demographic factors on this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The cutoff score used was 19. (16,17) For the assessment of Quality of Life, the Brazilian version of the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) was used. This is a generic instrument consisting of a comparative question about the current health status and that of one year ago, as well as 35 more items divided into 10 questions emphasizing the perception of people about their health in the last four weeks, and covering eight aspects: Functional Capacity, Physical Aspects, Pain, General Health Status, Vitality, Social Aspects, Emotional Aspects and Mental Health.…”
Section: Methodsmentioning
confidence: 99%
“…Running head: A PROGRAM TARGETING KEY GERIATRIC CONDITIONS 5 Studies identified shared risk factors for multiple geriatric conditions (Chen, et al, 2010;Inouye, et al, 2007). Based on a review of the literature, Inouye and colleagues (2007) identified that five common geriatric conditions, including pressure ulcers, incontinence, falls, functional decline, and delirium share four risk factors, which are: older age, cognitive impairment, functional impairment, and impaired mobility.…”
Section: Running Head: a Program Targeting Key Geriatric Conditionsmentioning
confidence: 99%
“…These conditions compound the complexity of acute illness and contribute to adverse outcomes and high mortality (Inouye, Bogardus, Baker, Leo-Summers, & Cooney, 2000). However, geriatric conditions are usually overlooked and left untreated in the acute care setting (Chen, et al, 2010;Inouye, et al, 2007). Although many other factors contribute to this situation, the health professionals' general lack of knowledge about these conditions has been identified as one of foremost factors (Chen, et al, 2010;Inouye, et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation